PENGARUH MEDIA AUDIOVISUAL TERHADAP KEMAMPUAN BERARGUMENTASI MAHASISWA PROGRAM STUDI SASTRA CHINA DALAM MATA KULIAH â€œCHINA TODAYâ€ - Yuk Ting Salim (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
The achievement of the level of language skills in learning Mandarin at the tertiary level is largely determined by the level of depth of knowledge received by students. The subject "China Today" is a listening course at the advanced level, where students must respond to Mandarin language discussions in the audiovisual media. Based on the field observations, it was found that there were two ways that are consistently used among students in presenting their arguments. The first is the delivery of short reviews and arguments that just repeat a few sentences according to what are they heard in the audiovisual media. The second is the submission of a complete review (covering all aspects mentioned in the audiovisual media), then followed by personal arguments. In the final listening process, as described by Tarigan, students should use the second way to present their arguments, to prove that they had achieved to the advanced level. The aim of this research is to identify which vocabulary was taken from audiovisual media, to analyze the effect of audiovisual media on students' ability in presenting arguments in the Mandarin language. Keywords: argumentative, audiovisual, Mandarin language, media